2019
DOI: 10.3390/ijerph16234873
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Analysis of Water Footprint and Economic Growth: A Case Study of Beijing–Tianjin–Hebei Region from 2004 to 2017

Abstract: The Beijing–Tianji–Hebei region (BTHR) is economically developed and densely populated, but its water resources are extremely scarce. A clear understanding of the decoupling relationship between water footprint and economic growth is conducive to facilitating and realizing the coordinated development of water resources and economic growth in this region. This study calculated the water footprint and other related indicators of BTHR from 2004 to 2017, and objectively evaluated the utilization of water resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…The continuous improvement of water efficiency in these two cities indicated that cities with higher water pressure would have a more urgent need for water-saving technology promotion and emphasis on water usage efficiency optimization [45]. This is consistent with previous studies in the Beijing-Tianjin-Hebei region, that is, cities with water scarcity would have advantages in water usage efficiency [7,34]. Besides, since a large amount of water were consumed in agriculture production, Beijing has reduced its localized agricultural production and gradually become a consumer-oriented city, which may also be the reason for Beijing to have the negative WF intensity effect [46].…”
Section: Decomposition Effect Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…The continuous improvement of water efficiency in these two cities indicated that cities with higher water pressure would have a more urgent need for water-saving technology promotion and emphasis on water usage efficiency optimization [45]. This is consistent with previous studies in the Beijing-Tianjin-Hebei region, that is, cities with water scarcity would have advantages in water usage efficiency [7,34]. Besides, since a large amount of water were consumed in agriculture production, Beijing has reduced its localized agricultural production and gradually become a consumer-oriented city, which may also be the reason for Beijing to have the negative WF intensity effect [46].…”
Section: Decomposition Effect Analysissupporting
confidence: 88%
“…However, only Beijing urban residents showed high demands for increased food consumption during the whole period. The growing food demand of Beijing residents could possibly be due to a higher living standard in this city, which has been indicated in other researches [7,34]. For the rural effect, the positive effects of Qingdao and Xiamen were reduced in the 2013-2018 period, reflecting a slow growth of food consumption level in Xiamen and a reduction in Qingdao.…”
Section: Food Consumption Level Effectmentioning
confidence: 62%
See 1 more Smart Citation
“…Its per capita water availability is as low as 5% of the world average and is decreasing annually. Its agricultural water use is 63% of the total water use [19,20]. In this area, winter wheat is the main water-intensive crop, and its production is highly dependent on irrigation with the extracted underground water.…”
Section: Introductionmentioning
confidence: 99%
“…The Yellow River-the country's second largest river basin-has been identified as a water-risk hotspot by the World Resources Institute [8]. Within this basin, the Beijing-Tianjen-Heibei region exhibited strong decoupling between water consumption and economic growth from 2004-2017, which was attributed to improved water-use efficiencies and conservation awareness on an individual scale, as researchers documented a substantial decline in the annual per-capita water footprint over this period [9]. Similarly, in a comparative urban review of China's three largest megacities for the period 2005-2015, Guangzhou was found to display the strongest decoupling between economic growth and water usage, followed by Shanghai and Beijing.…”
Section: Introductionmentioning
confidence: 99%